Outstanding in the rain [a whole story with holes] - Viva, Frank (Little, Brown & Co., 2015)
Rhyming text tells of a boy's birthday at Coney Island, while each turn of the page reveals a new meaning for an oronym...a pair of words or phrases which sound the same but have different spellings and meanings